Influence of Different Yeast Strains on Metabolism of Tryptophan and Indole-3-Acetic Acid During Fermentation - Mihaljević Žulj, M.; Tomaz, I.; Maslov Bandić, L.; Puhelek, I.; Jagatić Korenika, A.M.; Jeromel, A. (South African Journal of Enology and Viticulture, 2016)
The effect of supplementation of Riesling (Vitis vinifera L.) must with ammonium sulphate (AS) on tryptophan (Trp) and indole-3-acetic acid (IAA) metabolism during alcoholic fermentation with four commercial yeast strains (Uvaferm CEG, Lalvin Cross Evolution, Anchor VIN 13 and Anchor exotic SPH) were examined. AS addition reduced Trp uptake by yeasts from 1% to 15%. Wines produced by Anchor VIN 13 and Uvaferm CEG yeasts with AS addition had the highest concentrations of Trp (0.60 and 0.59 mg/L respectively). Concentrations of total and bound IAA decreased during all treatments. At the end of fermentation the highest concentration of free IAA was measured in the control must inoculated with Anchor VIN 13 yeast (35.83 μg/L) and the lowest in the sample inoculated with Uvaferm CEG yeast (13.08 μg/L). Anchor VIN 13 yeast showed the strongest change in metabolism due to AS addition during fermentation. 2-Aminoacetophenone (2-AAP) formation was not observed in all the studied wines.